Internationalization of the French Language Curriculum through the Application of the Common European Framework of Reference - Siti Umaya (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2023)
The research entitled “Internationalization of the French Language Curriculum through the Application of the Common European Framework of Reference (CEFR) is a descriptive study that aims to provide an overview of the internationalization of the French language curriculum in the French language study program STBA YAPARI ABA Bandung by adopting the CEFR. The form of implementation of the CEFR is carried out in several curriculum components, namely, graduate profiles, graduate learning outcomes (CPL), learning approaches and methods, as well as learning evaluations, especially assessments carried out on the four language skills, namely speaking skills (production orale), writing skills (production écrite)., listening skills (comprehension orale), and reading skills (comprehension écrite). The changes that occurred after the implementation of the CEFR were the addition of a minimum language competency standard of B1 CEFR as a graduate profile and learning outcomes. Furthermore, another change is the use of an action-based approach (actionnelle) and the addition of project-based learning, problem-based learning, and task-learning methods. AbstrakPenelitian yang berjudul “Internasionalisasi Kurikulum Bahasa Prancis melalui Penerapan Common European Framework of Reference (CEFR) merupakan penelitian deskriptif yang bertujuan untuk memberikan gambaran mengenai internasionalisasi kurikulum bahasa Prancis di prodi bahasa Prancis STBA YAPARI-ABA Bandung dengan mengadopsi CEFR. Bentuk penerapan CEFR tersebut dilakukan dalam beberapa komponen kurikulum yaitu profil lulusan, capaian pembelajaran lulusan (CPL), pendekatan dan metode pembelajaran, serta evaluasi pembelajaran khususnya penilaian yang dilakukan terhadap empat keterampilan berbahasa yaitu keterampilan berbicara (production orale), keterampilan menulis (production écrite), keterampilan mendengar (comprehension orale), dan keterampilan membaca (comprehension écrite). Perubahan yang terjadi setelah penerapan CEFR adalah penambahan standar kompetensi berbahasa minimal B1 CEFR sebagai dalam profil lulusan dan capaian pembelajaran. Selanjutnya, perubahan lainnya adalah penggunaan pendekatan berbasis tindakan (actionnelle) dan penambahan metode pembelajaran project-based learning, problem-based learning, dan tugas.Kata Kunci: Bahasa Prancis; CEFR; Internasionalisasi; Kurikulum